PERHITUNGAN DAN SOSIALISASI PAJAK PERTAMBAHAN NILAI YANG ADA PADA UMKM CV. X - Silitonga, Asnat T.; Sukma, Diah Ayu Permata; Marjani, Usi; Sutan, Naufal; Silmi, Silmi; Mazelfi, Ihsani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Value Added Tax, or VAT, is nothing new. Currently, many UMKM are subject to tax, such as CV.X. The Value Added Tax calculation available for UMKM can help UMKM in determining the amount of value added tax that must be paid by their company. This calculation is carried out in accordance with Tax Law Number 7 of 2021 concerning Harmonization of Tax Regulations. The calculated data is taken from previous transactions CV.X. Apart from that, this data was collected through direct interviews with owners of UMKM at CV.X. The main aim of preparing this article is to help UMKM in matters of taxation, especially regarding the existing Value Added Tax, for successful business continuity in the future. With a deep understanding of VAT and applicable tax regulations, it is hoped that MSMEs can optimize their financial management, minimize the risk of tax violations, and increase the competitiveness of their business in a competitive market. Through this article, it is hoped that MSMEs can achieve long-term success and contribute positively to overall economic growth.